The potential of blackcurrant, fig, and grape leaf extracts in the development of new preparations for overcoming antibiotic resistance and enhancing the efficacy of chemotherapeutic agents - Mikayel Ginovyan; Silvard Tadevosyan; Anahit Shirvanyan; Anush Babayan; Barbara Kusznierewicz; Izabela Koss-Mikołajczyk; Marika Mróz; Agnieszka Bartoszek; Naira Sahakyan (BMC Complementary Medicine and Therapies)
Abstract The presented study aimed to assess the efficacy of crude leaf hydroethanolic extracts from blackcurrant, fig, and grape leaves in reversing antibiotic resistance and enhancing chemotherapeutic efficacy. The viability tests were employed to assess the resistance-modifying properties of the extracts both in antibiotic-resistant bacterial cells and cancer cell-lines. To elucidate the potential mechanisms of the antibiotic modulatory activity of test extracts, the changes in H+-fluxes across the cell membrane and their impact on the H+-translocating F0F1-ATPase activity in antibiotic-resistant Escherichia coli explored. Qualitative metabolomic characterization of the extracts was performed using LC-Q-Orbitrap HRMS, and quantitative analysis was carried out with UHPLC-PDA. Experiments on doxorubicin-resistant and susceptible HT-29 cells revealed that all three extracts reversed antibiotic resistance in HT-29R cells, making them susceptible to doxorubicin in a dose-dependent manner. Notably, blackcurrant, and fig significantly reduced the minimum inhibitory concentrations of ampicillin and kanamycin against resistant E. coli strains. Our results indicated that all plant extracts enhanced H+-fluxes in the investigated bacterial strain and promoted ATPase activity, suggesting a potential role in altering bacterial membrane integrity. LC-Q-Orbitrap HRMS analysis identified more than 100 major peaks, with flavonoids and phenolics being the dominant constituents. The study underscores the potential of the selected plant extracts in developing of new agents to overcome antibiotic resistance and enhance the efficacy of chemotherapeutic agents. Importantly, although these plant leaves are often considered as bio-waste, they can be used as valuable sources of bioactive compounds. This underlines the importance of re-evaluating agricultural by-products for their potential in pharmacological applications, fostering a sustainable approach in drug development. Graphical Abstract